2017
DOI: 10.3354/esr00818
|View full text |Cite
|
Sign up to set email alerts
|

Environmental predictors of foraging and transit behaviour in flatback turtles Natator depressus

Abstract: Sea turtles migrate between nesting beaches and foraging grounds, but little is known about the cues they use to direct these migrations, and the habitats that define their foraging grounds. Here, we used satellite telemetry to follow the movements of 11 flatback turtles Natator depressus after nesting on islands in the waters off the coast of the Kimberley region of northern Australia. State-space models were used to objectively define inter-nesting, migration and foraging behaviour during the 327 ± 315 d (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Nevertheless, to overcome this issue the hDCRW-SSM takes into account the estimated error associated with each ARGOS LC (Jonsen et al, 2006), which ranges from 3000 m for LC B to 150 m for LC 3 (see Vincent et al, 2002;Jonsen et al, 2005 for details on how estimated errors are calculated). To incorporate GPS locations in the model, we assigned them the lowest ARGOS error (LC 3, <150 m), as per Thums et al (2017). The modeling parameters were as follows: we iterated one Markov chain Monte Carlo (MCMC) 300000 times, the first 100000 iterations were excluded (burn-in), every 100th of the remaining 200000 iterations was retained, and reconstructed locations were computed at 12-h intervals.…”
Section: Spatial Distribution Of Tracked Turtlesmentioning
confidence: 99%
“…Nevertheless, to overcome this issue the hDCRW-SSM takes into account the estimated error associated with each ARGOS LC (Jonsen et al, 2006), which ranges from 3000 m for LC B to 150 m for LC 3 (see Vincent et al, 2002;Jonsen et al, 2005 for details on how estimated errors are calculated). To incorporate GPS locations in the model, we assigned them the lowest ARGOS error (LC 3, <150 m), as per Thums et al (2017). The modeling parameters were as follows: we iterated one Markov chain Monte Carlo (MCMC) 300000 times, the first 100000 iterations were excluded (burn-in), every 100th of the remaining 200000 iterations was retained, and reconstructed locations were computed at 12-h intervals.…”
Section: Spatial Distribution Of Tracked Turtlesmentioning
confidence: 99%
“…Wildlife surveying has included size and abundance estimates of nesting bird colonies and seal haul-outs (Goebel et al 2015), dugong counts (Hodgson et al 2013), orangutan nest identification (Koh & Wich 2012), nesting behaviour of crocodiles (Evans et al 2015) and assessing spatial variation in abundance of reef sharks (Kiszka et al 2016). Furthermore, UAV data have been used to assess the effects that wildlife may have on their surroundings, such as changes to local landscapes post-beaver introduction (Puttock et al 2015) and crop damage by wild boar (Michez et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Foraging mostly occurs in continental waters off northern Australia, as well as in eastern Indonesia (Kai Islands to southern Papua) and southern Papua New Guinea (Hamann, Smith, & Preston, ; Limpus, ; Limpus, Parmenter, Baker, & Fleay, ; Pendoley, Schofield, Whittock, Ierodiaconou, & Hays, ; Suarez, ). Tagging studies indicate strong fidelity to nesting beaches (Limpus, ; Limpus, Fleay, & Baker, ; Pendoley et al, ), and tagging and satellite telemetry studies have indicated substantial breeding migrations of up to 1,650 km from nesting beaches (Hamann et al, ; Limpus et al, ; Pendoley, Schofield, et al, ; Thums et al, ). In the more southern extent of their nesting range, flatback turtles nest during the austral summer, whereas nesting at the northern rookeries occurs mostly during the austral winter (Limpus, ).…”
Section: Introductionmentioning
confidence: 99%